PENGARUH MODEL PROJECT-BASED LEARNING BERBASIS CANVA TERHADAP KREATIVITAS BELAJAR SISWA DI KELAS DIGITAL - Khairunnisa; Maya Safitri; Zainal Abidin (STKIP Subang, 2026)
The low level of student creativity in the digital classroom at MIN 3 Lhokseumawe, caused by the predominance of lecture-based teaching and a lack of interactive digital media, served as the background for this study. The objectives of this study are to: (1) describe how the Canva-based Project-Based Learning (PjBL) model is implemented in digital learning; (2) examine the increase in student creativity following the implementation of this model; and (3) examine the differences in learning creativity between students using the Canva-based PjBL model and those using traditional learning techniques. This study employed a pretest-posttest control group design, a quasi-experimental method, and a quantitative methodology. Sixty fifth-grade students from MIN 3 Lhokseumawe served as the research sample. Thirty students in the experimental class used a Canva-based PjBL methodology, while the other thirty students in the control class used traditional teaching methods. Exams and interviews were used as data collection methods. The results of the study showed that: (1) Student creativity increased after implementing the Canva-based PjBL model in a digital classroom, with the pre-test average score of 46.7 rising to 62.6 on the post-test (an increase of 15.9 points); (2) there was a significant difference in learning creativity between students who used the Canva-based PjBL model and those who used conventional learning, with a significance value of 0.001 (p < 0.05) and an effect size of 0.945 (large category). Thus, in digital classrooms, the Canva-based PjBL approach significantly and positively enhances students’ learning creativity.